Investigating the physical and chemical factors affecting the microbial status of water in the water distribution network of Babol City with an emphasis on the HPC index - Hossein Faraji; Hadi Rahimzadeh; Mehdi Salari; Zahra Aghalari; Fatemeh Asgharzadeh; Somayyeh Jafarian (PLoS ONE, 2025)
Background and purpose Safe and hygienic drinking water is crucial for public health. Secondary bacterial contamination, often caused by improper transport and distribution conditions, poses a significant threat. This study aimed to investigate the physical and chemical factors influencing the microbial status of drinking water in Babol’s distribution network, focusing on the heterotrophic plate count (HPC) index. Methods Thirty-two water samples were collected randomly from Babol’s rural areas and analyzed for HPC, residual free chlorine, turbidity, pH, and temperature. HPC was measured using the plate spreading technique on R2A agar. Descriptive statistics and regression analysis were employed to analyze the data. Findings Heterotrophic bacteria were detected in 61.4% of the samples, with 9.6% exceeding 500 CFU/ml. The average HPC was 140 CFU/ml, while residual free chlorine averaged 0.33 mg/l. In 21.4% of samples, residual chlorine was below 0.2 mg/l, and 19% had no detectable chlorine. Turbidity ranged from 0.05 to 3 NTU. Statistical analysis revealed significant positive correlations between HPC and pH, MPN, turbidity, and temperature (α < 0.05). Conclusion Regular HPC monitoring in Babol’s drinking water distribution network is essential to identify contaminated areas and ensure adequate residual free chlorine levels (0.2–0.8 mg/l) for maintaining bacteriological water quality.